Plant Viral Proteases: Beyond the Role of Peptide Cutters - Rodamilans, Bernardo; Shan, Hongying; Pasin, Fabio; García, Juan Antonio (Frontiers in Plant Science, 2018)
Almost half of known plant viral species rely on proteolytic cleavages as key co- and post-translational modifications throughout their infection cycle. Most of these viruses encode their own endopeptidases, proteases with high substrate specificity that internally cleave large polyprotein precursors for the release of functional sub-units. Processing of the polyprotein, however, is not an all-or-nothing process in which endopeptidases act as simple peptide cutters. On the contrary, spatial-temporal modulation of these polyprotein cleavage events is crucial for a successful viral infection. In this way, the processing of the polyprotein coordinates viral replication, assembly and movement, and has significant impact on pathogen fitness and virulence. In this mini-review, we give an overview of plant viral proteases emphasizing their importance during viral infections and the varied functionalities that result from their proteolytic activities.